Colonial nesting of the Hudson Bay eider duck - Schmutz, Josef K.; Robertson, Raleigh J.; Cooke, Fred (Canadian Journal of Zoology, 1983)
This study was designed to evaluate the factors influencing colonial nesting of the Hudson Bay eider duck (Somateria mollissima sedentaria). Colonial nesting reflected both selection of appropriate nesting habitat by female common eiders and advantages gained through social cooperation in predator defense. Female common eiders preferred to nest on small islands or on promontories near the shore and under shrubs of medium height. Nesting densities were greatest where a relatively large expanse of open water facilitated landing and taking flight. Nesting females gave alarm calls and formed dense flocks in response to a fox model. Egg predation was less in artificial nests which were close to an incubating female than in those situated further away. There was no correlation between degree of nesting synchrony and density of females on an island. Certain groups, however, exhibited greater nesting synchrony than expected by chance and the variance in egg shape among these females suggested that they were genetically related.